Біотоп як система: структура, динаміка, екосистемні послуги - Дідух, Я.П. (Український ботанічний журнал, 2018)
Концепція збереження біотичного та ландшафтного різноманіття сприяла проникненню системного та екологічного підходів у природоохоронну сферу, що стимулювало розробку класифікації біотопів. Біотопи розглядаються як екосистеми топологічного рівня, які при поділі втрачають просторову цілісність. Вони можуть включати різні, але функціонально поєднані між собою синтаксони, тобто обсяг топологічних і типологічних одиниць може не співпадати. Таке неспівпадіння можливе як через заміщення, так і поєднання складових одиниць. Заміщення відбувається у випадку, коли певні синтаксони входять до різних біотопів, або у різних регіонах певного біотопу спостерігається зміна синтаксонів. Наводяться приклади лісових (Dicrаno-Pinion, Fagion sylvaticae), болотних (Salicion cinereae) союзів, які входять до складу різних біотопів і приклади біотопів (G 3.9 Coniferous woodland dominated by Cupressaceae or Taxaceae, 8120 Temperate montane calcareous and ultra basic screes), у яких спостерігається заміщення союзів у різних регіонах. Поєднання проявляються у тому, що біотоп включає певний набір синтаксонів навіть різних класів. Розвиток біотопів зумовлений зміною екологічного потенціалу, що розглядається як невідповідність між потенційною ємністю екопростору, який визначається умовами зовнішнього середовища, та реальним його об'ємом, зумовленим структурою біотопу, характером розподілу біомаси, накопиченням та трансформацією енергії. Новизна такого підходу полягає в тому, що розвиток трактується ширше, ніж сукцесії фітоценозів, що зумовлені взаємодією між видами та їхнім впливом на зміну оточуючого середовища. Розвиток біотопу розглядається як процес флуктуаційних, сукцесійних та синеволюційних змін, що протікають з різною швидкістю і визначаються переважанням певних видів з різною стратегією (Grime, Pirs, 2012). Зокрема, флуктуацію визначають види R-, сукцесії – C-, синеволюцію – S-стратегії, що відбувається одночасно, але по-різному за різних умов і з різною швидкістю. Синеволюція зумовлена зміною адаптивних пристосувань та коеволюційних зв'язків видів по відношенню до змін зовнішніх умов, що веде до зміни ємності екопростору. Біотопи займають ключове положення в оцінці екосистемних послуг – вигоди для суспільства, що визначається не лише за економічними, а й екологічними критеріями. Хоча розрахунок повних екологічних послуг досить складний, проте розподіл біотопів за їхніми категоріями можна зробити на основі функцій екосистем, їхньої значимості з використанням певних допоміжних індикаторних ознак. Зокрема, визначальними для екосистемних послуг є переважаючі типи стратегії видів у біотопах (R-стратеги характеризують ресурсний, С-стратеги – функціональний, а S-стратеги – науково-інформаційний тип послуг). Найбільш вразливими до антропогенного впливу та кліматичних змін є біотопи функціонального типу, розвиток, яких визначається сукцесійними змінами, що вимагає розробки спеціальних заходів (менеджмент- плану) їхнього збереження. Концепция сохранения биотического и ландшафтного разнообразия способствовала проникновению системного и экологического подходов в природоохранную сферу, что стимулировало разработку классификации биотопов. Биотопы рассматриваются как экосистемы топологического уровня, которые при делении теряют пространственную целостность. Они могут включать различные, но функционально связанные между собой синтаксоны, то есть объем топологических и типологических единиц биотопа может не совпадать. Такое несовпадение обусловлено через замещение одних другими или новое сочетание составляющих единиц. Замещение происходит в случае, когда определенные синтаксоны проникают в состав иных биотопов, или в разных регионах определенного биотопа наблюдается изменение набора синтаксонов. Приводятся примеры лесных (Dicrаno-Pinion, Fagion sylvaticae), болотных (Salicion cinereae) союзов, входящих в состав различных биотопов и примеры биотопов (G 3.9 Coniferous woodland dominated by Cupressaceae or Taxaceae, 8120 Temperate montane calcareous and ultra basic screes), в которых наблюдается замещение союзов в разных регионах. Эффект сочетания проявляется в том, что биотоп включает определенный набор синтаксонов даже разных классов. Развитие биотопов обусловлено изменением экологического потенциала в случае несоответствия между потенциальной емкостью экопространства, которое определяется условиями внешней среды, и реальным его объемом, обусловленным структурой биотопа, характером распределения биомассы, накоплением и трансформацией энергии. Новизна такого подхода заключается в том, что процесс развития рассматривается шире, чем сукцессии фитоценозов, обусловленные взаимодействием между видами и их влиянием на изменение окружающей среды. Развитие биотопа рассматривается как процесс флуктуационных, сукцесийних и синэволюцийних изменений, протекающих с различной скоростью и определяются преобладанием определенных видов разных стратегий (Grime, Pirs, 2012). В частности, флуктуацию определяют виды R-, сукцессии - C-, синэволюцию - S-стратеги, что происходит одновременно, но по-разному в разных условиях и с разной скоростью. Синэволюция, обусловленная изменением адаптивных приспособлений и коэволюционных связей видов по отношению к изменениям внешних условий, ведет к изменению емкости экопросторанства. Биотопы занимают ключевое положение в оценке экосистемных услуг и определяются не только по экономическим, но и экологическим критериям. Хотя расчет полных экологических услуг достаточно сложный, однако оценку биотопов по их категориям можно сделать на основе функций экосистем, их значимости с использованием определенных вспомогательных индикаторных признаков. В частности, определяющими для экосистемных услуг являются доминирующие типы стратегий видов в биотопах (R-стратеги характеризуют ресурсный, С-стратеги – функциональный, а S-стратеги – научно-информационный тип услуг). Наиболее уязвимыми к антропогенному воздействию и климатическим изменениям являются биотопы функционального типа, развитие которых определяется сукцессионными изменениями, что требует разработки специальных мероприятий (менеджмент-плана) для их сохранения. The concept of conservation of biotic and landscape diversity facilitated the introduction of systemic and ecological approaches into the field of nature conservation, thus stimulating the development of biotope classification. Biotopes are considered to be ecosystems of a topological level, which lose their integrity once divided. Since biotopes can include distinct yet functionally interconnected syntaxa, the scope of topological and typological units that make up a biotope can differ. Such differences can be caused by substitution as well as combination of constituent elements. Substitution occurs when some syntaxa can be attributed to different biotopes, or when biotopes of the same type are comprised of different syntaxa. Examples of communities that are attributed to different biotopes, namely, forest (Dicrаno-Pinion, Fagion sylvaticae) and marsh (Salicion cinereae) communities, and examples of biotopes with substitution of constituent elements in some of their areas (G 3.9 Coniferous woodland dominated by Cupressaceae or Taxaceae, 8120 Temperate montane calcareous and ultra-basic screes) are given. Combination of constituent elements is evident when a biotope includes a certain set of syntaxa, which sometimes can belong to different classes. Biotope development is determined by the change in the ecological potential, which is interpreted as difference between the potential capacity of eco-space and its actual capacity. Potential capacity of eco-space is determined by the environment, whereas its actual capacity is determined by the biotope structure, nature of biomass distribution, and accumulation and transformation of energy. The novel aspect of this approach is that development is interpreted much wider than merely succession of phytocoenoses. Development is considered here as a process of fluctuating, successive, and synevolutional changes which occur at different rates and are defined by the predominance of certain species with various ecological (R, C, S) strategies (Grime, Pierce, 2012). Thus, species with R-strategy determine fluctuation, species with C-strategy determine succession, species with S-strategy define synevolution. Synevolution is caused by the changes in species’ adaptations and co-evolutionary relationships relative to environmental changes, thus altering eco-space capacity. Biotopes are integral to evaluation of ecosystem services. Predominant types of ecological strategies of species comprising biotopes are crucial for assessment of biotopes’ ecosystem services. Species with R-strategy are characteristic of the resource type of ecosystem services, species with C-strategy are characteristic of the functional type of ecosystem services, and species with S strategy are characteristic of scientific-informative type of ecosystem services. Biotopes of the functional type are most susceptible to anthropogenic impact and climate changes. Since development of functional biotopes is determined by the successive changes, appropriate measures, e.g., a management plan, are required for their conservation.